A new species of Acroleptus Bourgeois (Coleoptera: Lycidae) from the Brazilian Amazonian rainforest, with a note on its homonymy with Acroleptus Cabanis (Aves) - Ferreira, Vinicius S. (Zootaxa, 2015)
Acroleptus costae sp. nov. is described from the Brazilian Amazonian rainforest, raising the diversity of the formerly monotypic genus to two known species. The validity of Acroleptus Bourgeois, 1886 (Insecta) is maintained while Acroleptus Cabanis, 1861 (Aves) is considered to be an incorrect subsequent spelling.